2019
DOI: 10.1002/iub.2063
|View full text |Cite
|
Sign up to set email alerts
|

The potential therapeutic and prognostic impacts of the c‐MET/HGF signaling pathway in colorectal cancer

Abstract: Colorectal cancer (CRC) is the third most common cancer and a common cause of cancer‐related mortality globally. In spite of the improvements in the early diagnosis of CRC, approximately one‐third of patients develop metastasis and then have a very poor survival rate. The mesenchymal–epithelial transition factor (c‐MET) is a tyrosine kinase cell surface receptor activated by hepatocyte growth factor (HGF). Activation of c‐MET/HGF signaling pathway regulates a variety of biological processes including cell moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 68 publications
1
42
0
Order By: Relevance
“…Activation of HGF/MET can initiate downstream signalling pathways that drive malignant progression in many types of tumors. MET is considered an essential factor for early invasion and metastasis of CRC and can be regarded as an important prognostic indicator [17,18]. In the present study, we found that CREB5 promotes CRC invasion and metastasis by increasing MET expression to activate HGF-MET signalling.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Activation of HGF/MET can initiate downstream signalling pathways that drive malignant progression in many types of tumors. MET is considered an essential factor for early invasion and metastasis of CRC and can be regarded as an important prognostic indicator [17,18]. In the present study, we found that CREB5 promotes CRC invasion and metastasis by increasing MET expression to activate HGF-MET signalling.…”
Section: Introductionsupporting
confidence: 60%
“…Immunohistochemistry (IHC) staining was performed as previously described using CREB5 antibody (Abcam, USA, ab168928) [20]. The degree of IHC staining was reviewed and scored independently by two observers based on both the proportion of positively stained tumor cells and the intensity of staining [18,19]. The proportion of tumor cells was scored as follows: 0 (no positive tumor cells), 1 (< 10% positive tumor cells), 2 (10-50% positive tumor cells), and 3 (> 50% positive tumor cells).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Dysregulation of the MET signaling pathway occurs in a wide range of human cancers, including breast, colorectal, lung, pancreatic, hepatic, and ovarian cancers [39][40][41][42]. Inhibition of MET signaling has emerged as a promising approach for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, according to changes in dietary patterns and physical activity, CRC has dramatically increased in China [2]. Despite the advanced surgery technologies and medicine treatments have been applicated in CRC treatment, the survival rate of patients with CRC still remains unsatisfactory [3][4][5][6][7]. Hence, the mechanisms underlying CRC progression is urgent calling for new breakthrough.…”
Section: Introductionmentioning
confidence: 99%